Mechanical characterisation and modelling of a thermoreversible superamolecular polyurethane over a wide range of rates. (14th April 2021) - Chen, Huanming; Hart, Lewis R.; Hayes, Wayne; Siviour, Clive R.
Abstract: Understanding the mechanical response of thermo-recoverable elastomers to applied deformation at different strain rates and temperatures is crucial for more effective exploitation of these reusable materials in industrial applications. The research presented in this paper aims to understand the thermal and mechanical responses of a healable, elastomeric supramolecular polyurethane, examining morphology, rheology and mechanical responses from low to high strain rates. In particular, measurement of the high strain rate response of low modulus, or low strength, materials is challenging, and the current paper addresses this by incorporating a modelling framework based on low-rate characterization. To support this research, significant characterization experiments have been performed, which also show, for the first time, the excellent reusability of the polymer. The structure of specimens with different thermal histories was characterized using nuclear magnetic resonance spectroscopy, gel permeation chromatography and small angle X-ray scattering. Differential scanning calorimetry and Rheometry were used to investigate thermomechanical performance during heating and cooling cycles, whilst large strain compression characterization was performed on a commercial screw-driven test frame, a hydraulic loading system and a split-Hopkinson pressure bar. To describe the mechanical response of the polymer, a viscoelastic softening model was developed and characterized. The model incorporates data from rheometry and dynamic mechanical analysis using the principle of time-temperature superposition in a Prony series, combined with a non-linear large strain response, and recovery. The model was able to describe low strain rate behaviour under monotonic and cyclic loading, as well as predicting the response to monotonic loading at medium-to-high strain rates from 40 to 1220 s −1 . The paper therefore demonstrates the effectiveness of using the viscoelastic theory and its analytical model to calibrate and further predict the mechanical behaviour of polymers at different strain rates: this is particularly useful for low modulus materials for which high strain rate characterization is challenging. Graphical abstract: Image 1 Highlights: Characterization and modelling of a supramolecular polyurethane with healing capability. Structural and mechanical properties measured using wide range of techniques. Data show consistent response over multiple thermal cycles: reusability and recyclability. Model predicts high-rate response from static data, avoiding high strain rate characterization.